Time from HIV seroconversion to death: A collaborative analysis of eight studies in six low and middle-income countries before highly active antiretroviral therapy - Jim Todd (2018)
OBJECTIVES: To estimate survival patterns after HIV infection in adults in low and middle-income countries. DESIGN: An analysis of pooled data from eight different studies in six countries. METHODS: HIV seroconverters were included from eight studies (three population-based, two occupational, and three clinic cohorts) if they were at least 15 years of age, and had no more than 4 years between the last HIV-negative and subsequent HIV-positive test. Four strata were defined: East African cohorts; South African miners cohort; Thai cohorts; Haitian clinic cohort. Kaplan-Meier functions were used to estimate survival patterns, and Weibull distributions were used to model and extend survival estimates. Analyses examined the effect of site, age, and sex on survival. RESULTS: From 3823 eligible seroconverters, 1079 deaths were observed in 19 671 person-years of follow-up. Survival times varied by age and by study site. Adjusting to age 25-29 years at seroconversion, the median survival was longer in South African miners: 11.6 years [95% confidence interval (CI) 9.8-13.7] and East African cohorts: 11.1 years (95% CI 8.7-14.2) than in Haiti: 8.3 years (95% CI 3.2-21.4) and Thailand: 7.5 years (95% CI 5.4-10.4). Survival was similar for men and women, after adjustment for age at seroconversion and site. CONCLUSION: Without antiretroviral therapy, overall survival after HIV infection in African cohorts was similar to survival in high-income countries, with a similar pattern of faster progression at older ages at seroconversion. Survival appears to be significantly worse in Thailand where other, unmeasured factors may affect progression. © 2007 Lippincott Williams & Wilkins, Inc.